Chemical Seed Priming: Molecules and Mechanisms for Enhancing Plant Germination, Growth, and Stress Tolerance - Mason T. MacDonald; Vijaya R. Mohan (Current Issues in Molecular Biology)
Food security is one of the world’s top challenges, specifically considering global issues like climate change. Seed priming is one strategy to improve crop production, typically via increased germination, yields, and/or stress tolerance. Hydropriming, or soaking seeds in water only, is the simplest form of seed priming. However, the addition of certain seed priming agents has resulted in a variety of modified strategies, including osmopriming, halopriming, hormonal priming, PGR priming, nutripriming, and others. Most current research has focused on hormonal and nutripriming. This review will focus on the specific compounds that have been used most often over the past 3 years and the physiological effects that they have had on crops. Over half of recent research has focused on four compounds: (1) salicylic acid, (2) zinc, (3) gibberellic acid, and (4) potassium nitrate. One of the most interesting characteristics of all chemical seed priming agents is that they are exposed only to seeds yet confer benefits throughout plant development. In some cases, such benefits have been passed to subsequent generations, suggesting an epigenetic effect, which is supported by observed changes in DNA methylation and histone modification. This review will summarize the current state of knowledge on molecular changes and physiological mechanisms associated with chemical seed priming agents and discuss avenues for future research.